2016
DOI: 10.1038/srep25903
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cerebral blood flow and oxygen metabolism in extremely preterm neonates with low-grade germinal matrix- intraventricular hemorrhage

Abstract: Low-grade germinal matrix-intraventricular hemorrhage (GM-IVH) is the most common complication in extremely premature neonates. The occurrence of GM-IVH is highly associated with hemodynamic instability in the premature brain, yet the long-term impact of low-grade GM-IVH on cerebral blood flow and neuronal health have not been fully investigated. We used an innovative combination of frequency-domain near infrared spectroscopy and diffuse correlation spectroscopy (FDNIRS-DCS) to measure cerebral oxygen saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 63 publications
3
46
0
1
Order By: Relevance
“…7,28 Increases in physiologic stress and metabolic demand, either in utero or during the early extrauterine life, may exceed the ability of the increase in cerebral blood flow. 7 Our finding of decreased CBF in PT infants with BI corroborates a previous study by Lin et al, 29 using near-infrared spectroscopy and diffuse correlation spectroscopy imaging. However, ASL-MR imaging has an advantage over the previous method because it is a direct quantitative technique for assessing cerebral perfusion.…”
Section: Discussionsupporting
confidence: 90%
“…7,28 Increases in physiologic stress and metabolic demand, either in utero or during the early extrauterine life, may exceed the ability of the increase in cerebral blood flow. 7 Our finding of decreased CBF in PT infants with BI corroborates a previous study by Lin et al, 29 using near-infrared spectroscopy and diffuse correlation spectroscopy imaging. However, ASL-MR imaging has an advantage over the previous method because it is a direct quantitative technique for assessing cerebral perfusion.…”
Section: Discussionsupporting
confidence: 90%
“…In another study of extremely preterm neonates, the subjects with hemorrhage were found to have lower CBF when compared with those without hemorrhage (Lin et al , 2016). Similarly, lower CBF levels in neonates with hypoxic ischemic encephalopathy were reported, compared to age-matched healthy neonates (Dehaes et al , 2014).…”
Section: Clinical Application Examplesmentioning
confidence: 99%
“…DCS/DCT technologies have been extensively explored to be used in animal models and human subjects for the diagnosis and therapeutic monitoring of diseases in various tissues and organs including brains (Cheng et al , 2014; Hou et al , 2014; Busch et al , 2016a; Kim et al , 2014; Kim et al , 2010; Favilla et al , 2014; Lin et al , 2016; Dehaes et al , 2014; Durduran et al , 2010b; Shang et al , 2011b; Buckley et al , 2013; Zirak et al , 2014), skeletal muscles (Henry et al , 2015; Mesquita et al , 2013; Yu et al , 2005a; Shang et al , 2012; Gurley et al , 2012), and tumors (Chung et al , 2015; Choe et al , 2014; Zhou et al , 2007; Durduran et al , 2005; He et al , 2015; Sunar et al , 2006; Dong et al , 2012b; Dong et al , 2016). Since this review focuses on the clinical applications, only typical clinical examples are presented in the following subsections based on different types of tissues/organs.…”
Section: Clinical Application Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…red blood cells and a physical model can be utilized to relate this to a blood flow index (BFI) [15]. DCS has been validated against different standard techniques for blood flow measurement [16] and it has been employed in a variety of studies on infants [17][18][19][20][21][22].…”
mentioning
confidence: 99%